EKSPLORASI ETNOMATEMATIKA PADA BENTUK KETUPAT DALAM TRADISI REBO WEKASAN DAN RELEVANSINYA DENGAN PEMBELAJARAN MATEMATIKA DI SD - Resa Syam Rahmawati; Ani Siti Anisah; Ade Holis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Mathematics holds an important position in the field of education, especially in elementary schools. Mathematics in elementary schools, especially in geometry material, can be more contextual and represented through the ketupat form in the Rebo Wekasan tradition. This study aims to explore ethnomathematics in the ketupat form in the Rebo Wekasan tradition and its relevance in mathematics learning. The method applied is the approach used in this study is a descriptive qualitative approach. Data were collected through various methods such as observation, interviews, and documentation. Data analysis was carried out through several stages, namely data collection, data reduction, data presentation, drawing conclusions and verification. This study found that ethnomathematics in the form of ketupat in the Rebo Wekasan tradition is related to mathematics and is relevant to geometry material in elementary schools which can be used as a learning medium that is relevant to everyday life to help students, especially grade 3, to better understand the material being taught.